RIESGOS ASOCIADOS AL USO DE PANTALLAS DE VISUALIZACION DE DATOS EN TRABAJADORES DE MEDIANAS EMPRESAS DEL ESTADO DE HIDALGO - Tirso Javier Hernández Gracia; Enrique Muñoz Martínez; Fernando Castillo Gallegos; Germán Sánchez Monjaraz (European Scientific Journal, ESJ, 2015)
The article intends to analyze the risks associated to the use of display units of information (diu´s) in workers of medium companies of hidalgo state, in order to recognize trends related to the main diseases derived from it. The offices’ modernization with new technologies must consider also the furniture, the connections and comfortable environment, as well as, that the personnel should take the preventive measurements to avoid suffering deteriorations in his health through time. We obtained results from a 400 workers study which came from different administrative areas of 20 companies, which reflect that more than 70% of workers don’t count with ideal furniture characteristics for computer equipment, more than 80% don’t have sufficient space, illumination, facilities, wiring and appropiate ventilation, and in some cases more than 50% suffers already visual problems and headaches, between other symptoms.